The possible role of mRNA expression changes of GH/IGF-1/insulin axis components in subcutaneous adipose tissue in metabolic disturbances of patients with acromegaly - Toušková, Věra; Kloučková, Jana; Ďurovcová, Viktória; Lacinová, Zdeňka; Kaválková, Petra; Trachta, Pavel; Kosák, Mikuláš; Mráz, Miloš; Haluzíková, Denisa; Hána, Václav; Marek, Josef; Kršek, Michal; et al. (Physiological research, 2016)
We explored the effect of chronically elevated circulating levels of growth hormone (GH)/insulin-like-growth-factor-1 (IGF-1) on mRNA expression of GH/IGF-1/insulin axis components and p85alpha subunit of phosphoinositide-3-kinase (p85alpha) in subcutaneous adipose tissue (SCAT) of patients with active acromegaly and compared these findings with healthy control subjects in order to find its possible relationships with insulin resistance and body composition changes. Acromegaly group had significantly decreased percentage of truncal and whole body fat and increased homeostasis model assessment-insulin resistance (HOMA-IR). In SCAT, patients with acromegaly had significantly increased IGF-1 and IGF-binding protein-3 (IGFBP-3) expression that both positively correlated with serum GH. P85alpha expression in SCAT did not differ from control group. IGF-1 and IGFBP-3 expression in SCAT were not independently associated with percentage of truncal and whole body fat or with HOMA-IR while IGFBP-3 expression in SCAT was an independent predictor of insulin receptor as well as of p85alpha expression in SCAT. Our data suggest that GH overproduction in acromegaly group increases IGF-1 and IGFBP-3 expression in SCAT while it does not affect SCAT p85alpha expression. Increased IGF-1 or IGFBP-3 in SCAT of acromegaly group do not appear to contribute to systemic differences in insulin sensitivity but may have local regulatory effects in SCAT of patients with acromegaly.
Keywords: Class Ia Phosphatidylinositol 3-Kinase; mužské pohlaví; lidský růstový hormon; Insulin-Like Growth Factor I; Male; Insulin Resistance; Female; Humans; fosfatidylinositol-3-kinasy třídy Ia; lidé; Middle Aged; ženské pohlaví; lidé středního věku; Acromegaly; Insulin; inzulinová rezistence; Subcutaneous Fat; studie případů a kontrol; Case-Control Studies; akromegalie; messenger RNA; podkožní tuk; inzulin; Human Growth Hormone; insulinu podobný růstový faktor I; dospělí; IGFBP-3; Adult; Insulin-Like Growth Factor Binding Protein 3; RNA, Messenger